2015
DOI: 10.1039/c4nj01642d
|View full text |Cite
|
Sign up to set email alerts
|

Novel triazole-based ligands and their zinc(ii) and nickel(ii) complexes with a nitrogen donor environment as potential structural models for mononuclear active sites

Abstract: A tridentate N,N,N-1,2,3-triazole-based ligand successfully coordinated to nickel ions through the less Lewis basic N2 atom of the triazole ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…On the one hand, a survey of the CSD revealed that, in the few known penta-coordinated [Zn­(R-bpa)­Br 2 ] complexes, the bpa ligand is bound to the central metal as mer -isomer. ,,,, On the other hand, even for a significantly broader class of compounds, namely, [M­(R-bpa)­X 2 ] complexes containing any transition metal M or any halogen ions X, the bpa fac -isomer was found relatively rarely in the solid state, with only a handful of structures in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, a survey of the CSD revealed that, in the few known penta-coordinated [Zn­(R-bpa)­Br 2 ] complexes, the bpa ligand is bound to the central metal as mer -isomer. ,,,, On the other hand, even for a significantly broader class of compounds, namely, [M­(R-bpa)­X 2 ] complexes containing any transition metal M or any halogen ions X, the bpa fac -isomer was found relatively rarely in the solid state, with only a handful of structures in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…The function of the 1,2,3-triazolyl moiety, derived from copper(I)-catalysed azide−alkyne cycloaddi on (CuAAC), has recently been expanded to coordination chemistry of transition metals. [1][2][3][4][5][6] Regioselective formation of 1,4-disubstituted 1,2,3triazole-based mono-, bi-or multidentate chelating ligands has received considerable attention because of its broad application in drug development, optics, redox sensing, fluorescence and catalysis. 2,3,[7][8][9][10][11][12][13] The large dipole moment of triazoles, around 5 D, allows easy formation of hydrogen bonds, as well as dipoledipole and π-interactions, which can favour their binding to biological targets and improve their solubility.…”
Section: Introductionmentioning
confidence: 99%
“…They are linked to diverse applications of primary importance in biology, medicine, industry, environment, and material science. In biology and medicine, 1,2,3-triazole@Zn 2+ complexes are potentially used to mimic the histidine-carboxylate active site of metallopeptidases, which is connected with the catalytic conversion of CO 2 in biological media. We can also find these entities in antibacterial drugs. Indeed, amitrole (3-amino-1,2,4-triazole) is a widely used herbicide that inhibits an enzyme of histidine biosynthesis in Salmonella typhimurium .…”
Section: Introductionmentioning
confidence: 99%